Diboranyl phosphonium cations: synthesis and chemical properties - Litters, Sebastian; Ganschow, Michael; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2015)
Abstract Hydride abstraction from the diborane [HB(hpp)]2 (hpp = 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate) followed by base stabilization led to the first (highly water sensitive) diboranyl phosphonium cations of the general formulas [HB(hpp)2BPR3]+ and [HB(hpp)2BPHR2]+. The B?P bond strength could be varied over a relatively large range by choice of the substituents R on the phosphine. The cation [HB(hpp)2BPCy3]+ (Cy = cyclohexyl) was structurally characterized. The PCy3 base of this cation could be substituted by a stronger base (a carbene or a bicyclic guanidine). In solution, [HB(hpp)2BPCy3]+ very slowly decomposes, and [HB(hpp)3BH]+ was identified as one of the decomposition products.
Gesehen am 26.06.2020